Microsoft SharePoint 2010 : building solutions for SharePoint 2010 - Malik, Sahil (New York : Apress, 2010)
"This book provides a fresh take on Microsoft's premier collaboration solution. A critical resource if you're developing on the SharePoint platform, this book features a complete focus on the new features and capabilities of SharePoint 2010. Through a thorough treatment of sites, web parts, data management, portal solutions, and business intelligence capabilities, you'll appreciate author Sahil Malik's concise yet highly readable text"--Resource description p.
Includes bibliographical references and index.
Keywords: Intranets (Computer networks); Web servers